2022
DOI: 10.1021/acsami.2c07638
|View full text |Cite
|
Sign up to set email alerts
|

Co-Doped Zeolite–GO Nanocomposite as a High-Performance ORR Catalyst for Sustainable Bioelectricity Generation in Air-Cathode Single-Chambered Microbial Fuel Cells

Abstract: High-performance cobalt (Co) nanoparticles supported on a zeolite–graphene oxide (1:2) matrix (catalyst Z2) are synthesized through a facile reduction method. In multipoint Brunauer–Emmett–Teller (MBET) surface area analysis, catalyst Z2 demonstrates a higher surface area compared with other synthesized catalysts, indicating the presence of a larger number of catalytic active sites, and supports outstanding ORR performance due to an improved electron-transfer rate and a higher number of redox-active sites. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…4, the I D / I G of MoO 2 /Mo 2 C/C was 1.75, which was higher than the I D / I G (1.39) of the MoO 2 /Mo 2 C and the I D / I G (1.06) of Vulcan XC-72R, which indicated that the composition of the transition metal compound MoO 2 /Mo 2 C did improve the ORR electron transfer ability of the MoO 2 /Mo 2 C/C. 29,30…”
Section: Resultsmentioning
confidence: 93%
“…4, the I D / I G of MoO 2 /Mo 2 C/C was 1.75, which was higher than the I D / I G (1.39) of the MoO 2 /Mo 2 C and the I D / I G (1.06) of Vulcan XC-72R, which indicated that the composition of the transition metal compound MoO 2 /Mo 2 C did improve the ORR electron transfer ability of the MoO 2 /Mo 2 C/C. 29,30…”
Section: Resultsmentioning
confidence: 93%
“…Silicalite zeolite, having slit-like mesopores (size of 2.0 to 2.5 nm), has also been developed by the addition of graphene oxide nanosheets throughout the synthesis and subsequent calcination of synthesized samples. Cationic polyelectrolyte functionalized GO was synthesized by the hard template method via incorporation of poly­(diallyl dimethylammonium chloride) (PDDA) into GO, which leads to the formation of slit-like mesopores throughout both sides of the GO surface. The synthesized nanoporous zeolite-Y and zeolite-Y/GO nanocomposites were then examined for their water adsorption capacity. …”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Bio-electrochemical systems (BESs) are devices which contain microorganisms to donate or accept electrons from an electrode. The performance of any BES is affected by many factors, where microbes and anodes play a very crucial role. , The extent of microbial–electrode interaction is the rate-limiting factor that determines the performance of the BES. In regard to enhanced microbial activity and extracellular electron transfer (EET), a desired anode with selective adhesion of microbes and that provides more sites for microbial adhesion and electron transfer is mandatory .…”
Section: Introductionmentioning
confidence: 99%